Breastfeeding Self Efficacy Dapat Meningkatkan Produksi Asi Pada Ibu Post Partum - Lutfiana Puspita Sari; Lusinta Agustina (Interest : Jurnal Ilmu Kesehatan, 2019)
Background: The Confidence, perception and calmness of post-partum mothers can affect the breastmilk production. Women who have low anxiety will have greater self-efficacy indeed believe that breast milk production is sufficient for the baby's needs. Method: This was a quantitative research with survey design. The population in this study was all post-partum mothers who gave birth in a normal process. The sample in this study was all post-partum mothers who were giving birth normally at the Independent Practice of Midwives at the Prambanan Health Center, Klaten. The analysis of this study used the Fisher Exact test. Result: There was a significant effect between breastfeeding self-efficacy on the amount of breastmilk production (p-value = 0.03), breastfeeding self-efficacy on the process of breastmilk production (p-value = 0.01). Conclusion: Breastfeeding self-efficacy influences the amount and process of breastmilk production for post-partum mothers